Improving Breviscapine Oral Bioavailability by Preparing Nanosuspensions, Liposomes and Phospholipid Complexes - Zilin Song; Jiaojiao Yin; Peifu Xiao; Jin Chen; Jingxin Gou; Yanjiao Wang; Yu Zhang; Tian Yin; Xing Tang; Haibing He (MDPI AG, 2021)
Breviscapine (BVP), a flavonoid compound, is widely used in the treatment of cardiovascular and cerebrovascular diseases; however, the low oral bioavailability and short half-life properties limit its application. The aim of this study was to investigate the three preparations for improving its oral bioavailability: nanosuspensions (BVP-NS), liposomes (BVP-LP) and phospholipid complexes (BVP-PLC). In vitro and in vivo results suggested that these three could all significantly improved the cumulative released amount and oral bioavailability compared with physical mixture, in which BVP-PLC was the most optimal preparation with the relative bioavailability and mean retention time of 10.79 ± 0.25 (p < 0.01) and 471.32% (p < 0.01), respectively. Furthermore, the influence of drug-lipid ratios on the in vitro release and pharmacokinetic behavior of BVP-PLC was also studied and the results showed that 1:2 drug-lipid ratio was the most satisfactory one attributed to the moderate-intensity interaction between drug and phospholipid which could balance the drug loading and drug release very well.